Hysteresis of superconducting cylinder in transverse magnetic field. - Zhilichev, Y.N (IEEE Transactions on applied superconductivity)
A piecewise continuous distribution of critical currents is used to predict the hysteresis of the superconducting cylinder in the transverse magnetic field slowly oscillating in time. The proposed hysteresis model takes into account that the magnetic field has the peripheral and radial components due to the screening effect of critical currents. The model is used to predict the hysteresis loss in a round superconducting wire. An analytical formula for the hysteresis loss is given